Mengefektifkan Kegiatan Keagamaan Majelis Taklim di Panti Sosial Tresna Werdha Tribuana Tunggal Dewi Lingkungan Balongrawe Kelurahan Kedundung Kecamatan Magersari Kota Mojokerto - Mustain, Mustain (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
The existence of majelis taklim felt increasingly important and expected to play a bigger role in addressing various problems arising in the community. However, in organizing and managing its activities, not a few problems and obstacles faced by majelis taklim. It is quite a lot of faced is the management aspects, organization, and administration are weak and less systematic review and quality of human resources (HR) is still limited. One of the root of the problem is the lack of a proselytizing missionary or ustadzah who is able to provide good, systematic and qualified congregations. The purpose of this study are: 1) Describe religious activities majelis taklim in Social House Tresna Werdha Tribuana Tunggal Dewi. 2) Describe the obstacles in the effectiveness of religious activities majelis taklim in Social House Tresna Werdha Tribuana Tunggal Dewi. This study is a research Community-based parcipatory research (CBPR) Researchers directly jumped to make changes, and see the changes that occur. The research data used is secondary data. Data collection techniques used are documentation and observation. Data analysis in this research is done during and after data collecting by using descriptive-critical-comparative method, and content analysis method. From the explanation described, it is concluded: 1) Religious Activity Program of Majelis Taklim made the residents of Social House Tresna Werdha Tribuana Tunggal Dewi Environment Balongrawe Kelurahan Kedundung Magersari Subdistrict Mojokerto City is enthusiastic in following and deepening the religious knowledge of Islam. 2) The obstacles encountered are locations that are less representative of the narrow musholla and temat wudlu which he only point. While the people who built a lot of wide enough practice practice or praying in congregation menajadi constrained